Pengaruh Sikap Asertif Guru Terhadap Pembentukan Perilaku Prososial Pada Anak Usia Dini di RA Kecamatan Bojongsoang - Azahra, Raissa Selfi; Marisa, Rita Oktafil; Permanik, Intan (Institut Agama Islam Persis Bandung, 2025)
Prosocial behavior refers to children’s ability to help, cooperate, share, and demonstrate empathy toward others. As the primary educators in early childhood settings, teachers play a crucial role in fostering prosocial behavior through assertive communication. This study aims to examine the influence of teachers’ assertive attitudes on the development of prosocial behavior among early childhood learners in RA institutions in Bojongsoang District. The research employed a quantitative approach with an explanatory survey design. The study population consisted of 13 RA institutions with a total of 89 teachers, and a sample of 59 teachers was selected using purposive sampling. Data were collected using a Likert-scale questionnaire that had been validated and tested for reliability. Data analysis was conducted using simple linear regression. The findings show that teachers’ assertive attitudes fall into the high category (TCR = 88.3%), as does children’s prosocial behavior (TCR = 93.5%). Regression analysis indicates a significant influence of teachers’ assertive attitudes on children’s prosocial behavior (F = 81.322; sig = 0.000). The coefficient of determination reveals that 69.6% of the variance in children’s prosocial behavior is explained by teachers’ assertive attitudes, indicating a strong contribution.These findings imply that assertive, empathetic, and child-respecting teacher communication practices must be strengthened in daily learning activities to enhance the quality of social interactions among young children.